Pemberitaan Kemenangan Pasangan Gatot Pujo Nugroho – Tengku Erry Nuradi (Ganteng) Dalam Hasil Hitung Cepat Pemilukada Sumatera Utara 2013 Pada Harian Analisa Dalam Perspektif Analisis Wacana Kritis - Abdul Muamar (FLOW, 2013)
The results of North Sumatera’s election is something that is always awaited by the society. Therefore, the announcement of the quick count results of the regional election conducted by surveillance institutions has become a good materials for news in some medias. By Analisa Daily, the results of the regional election was created to be a discourse that contained certain ideology. This research raised up the discourse as the object tittled “Pemberitaan Kemenangan Pasangan Gatot Pujo Nugroho – Tengku Erry Nuradi (Ganteng) Dalam Hasil Hitung Cepat Pemilukada Sumatera Utara 2013 Pada Harian Analisa Dalam Perspektif Analisis Wacana Kritis” which study how the Analisa daily creates the discourse about Ganteng’s victory. The goal of this research is to find the answer about how a domination practice is occuring behind the discourse. It goes from a critical view which puts a discourse not as something that is normally occuring. The language within this view, is seen as a main tool to run a targetted social practice. This research uses the Norman Fairclough’s critical analysis methode to gain the information about how media creates the discourse. By this method, the discourse is analized within three levels, which are text analysis, discourse practice analysis, and sociocultural practice analysis. Each level are related to each other. At the end of the result, this research finds that there is a tendention of Analisa daily to be in Ganteng’s side. It is seen from the analysis on the representation, relation, identity, and intertextuality of the text. Meanwhile, the deep interview also tells us the same. Keywords: Analisa Daily, North Sumatera’s election, Quick Count, Discourse.